Effect of Cr3C2 Content on Microstructure and Properties of Laser Cladding Ti(C, B)/Ni Coatings - Yunlong, Liang; Hanguang, Fu; Zhenguo, Xing; Xingye, Guo; Jian, Lin (Journal of materials engineering and performance, 2022)
In order to solve the problems of low hardness and poor wear resistance of titanium alloy, laser cladding technology was used to prepare Ti(C,B)/Ni coatings with different amount of Cr 3 C 2 on the surface of Ti-6Al-4V titanium alloy. The effects of Cr 3 C 2 content on the microstructure, hardness and wear resistance of Ti(C,B)/Ni coating were investigated by methods of scanning electron microscope (SEM), x-ray diffractometer (XRD), microhardness tester and M-200 wear tester. The results showed that phases existing in coating mainly contain γ-Ni, Ni 3 Ti, NiTi, TiB 2 , Ti(C,B) and CrB. With the increase of Cr 3 C 2 content, the size and number of black bulk precipitates in the coating reduced. Meanwhile, the short rod-like Ti(C,B) particles grew and the amount of the particles increased, and Ti(C,B) particles existed in the form of cellular dendritic crystals in the coating. The average microhardness of the cladding layer without Cr 3 C 2 addition is 896.7 HV 0.2 , which is about 1.5 times higher than that of Ti-6Al-4V substrate (360 HV 0.2 ). With the increase of Cr 3 C 2 content (10, 20, 30 wt.%), the average microhardness of the coating increased to 948.7, 990.4 and 1035.8 HV 0.2 , respectively. The average hardness of the coating added 30 wt.%Cr 3 C 2 is 15.5% higher than that of the Cr 3 C 2 -free coating. At the same time, the wear resistance increased with the increase of Cr 3 C 2 content.